DEXA as a Predictor of Fixator Removal in Distraction Osteogenesis - Saran, Neil (Springer-Verlag, 2008)
Premature removal of the fixator after a lengthening procedure can result in gradual bending or acute fracture of the regenerate. We reviewed the records of 26 patients who underwent 28 limb lengthenings between 1997 and 2005 to assess the post lengthening regenerate fracture rate and bone healing index when using dual energy xray absorptiometry (DEXA) to aid in deciding on when to remove the fixator. Sixteen male and 10 female patients with an average age at lengthening of 12.3 years underwent an average lengthening of 5.2 cm (range, 3–9.1 cm). Nineteen femurs and nine tibiae were lengthened. Serial monthly DEXA scans were analyzed for bone mineral density. Bone healing indices and post fixator removal complications were assessed. The fixators were removed once the bone mineral density had plateaued to a less than 10% increase and plain radiographs showed no obvious defects precluding fixator removal. There were no regenerate fractures and only one fracture in the proximal segment of the lengthened bone after apparatus removal and the healing index for the series averaged 47 d/cm (range, 20–73 d/cm). Using serial DEXA scans during the consolidation phase of lengthening has a low rate (3.6%) of fractures while maintaining an acceptable bone healing index without excessively increasing fixation time. Level of Evidence: Level IV, therapeutic retrospective study. See the Guidelines for Authors for a complete description of levels of evidence.